Kesopanan Berkomunikasi Dalam Wawancara NCT Dream Bersama Ggondaehee - Siti Naimah; Nina Yuliana (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
This study analyzes the language and behavioral politeness in the interaction between NCT Dream members Renjun and Jeno and host Ggondaehee on the show "Let's Eat." This study adopts Brown and Levinson's politeness theory, which includes strategies for maintaining positive and negative face and managing potentially face-threatening acts (FTAs). The purpose of this study is to understand how politeness strategies are applied in maintaining positive and negative face and managing FTAs in the interaction. The research method used is descriptive qualitative with video analysis as the main data source. The results show that Renjun and Jeno respond to FTAs from Ggondaehee with politeness strategies that reflect respect and politeness, such as waiting for Ggondaehee to start eating and responding to compliments in a friendly manner. Ggondaehee used on-record and off-record FTA strategies to manage the interaction, such as giving direct orders and using humor. This study found that positive and negative politeness strategies were used effectively by both parties to maintain the harmony of the interaction and avoid conflict.